Analisa Kritis Terhadap Praktek Accounting Creative dalam Perusahaan yang Berbudaya Syariah (Studi Kasus pada Layanan Kesehatan yang Berbudaya Syariah) - Wirawan Hardinto (Jurnal Aplikasi Bisnis, 2017)
There are some factors that influence the corporation on to do creative accounting. They are financial statement users who tend to see only on the net income at income statements, flexibility in Financial Accounting Standard and the cultural who have an influence to all elements in the organization. Accounting creative has variety interpretations, some interpret it positively, and the others negatively, in the positive interpretation, it's corporation activity who uses Accounting technic and policy to achieve a corporation's result, or legal technic based on accounting rules or accounting standard. In the corporate culture contexs, creative accountings is an important management instruments which can be infiuenced by corporate culture.Corporation has some motivations, while running the creative accounting, they are politic motivation, tax, bonus, loans and CEO replacement. This paper focuses on how the form of accounting creative's practice in the corporation which has cultural based on shariah. In the shariah cultural corporation, accounting creative's practice adopts a legal technic which based on accounting rules or accounting standard.